THE INFLUENCE OF TRAINING ON WORK PRODUCTIVITY THROUGH WORK ENGAGEMENT AND COMPETENCE OF OIL PALM FARMERS - Matias Yoq; E. Didik Subiyanto; Syamsul Hadi (Jurnal Apresiasi Ekonomi, 2025)
This study aims to examine the effect of training on work productivity through work engagement and competence of oil palm farmers in Nehas Liah Bing Vilage, East Kutai Regency, involving 100 participants. The sample in this study consists of individuals working as oil palm farmers, supported by the Sumber Usaha Kel'an Blom Kejah Cooperative in Nehas Liah Bing Village. Data were collected through questionnaires using a Likert scale, which were then processed using Microsoft Excel 2019, SPSS version 26, and SmartPLS 3 software. The sampling technique used in this research was Non-Probability Sampling with Saturated Sampling. The research method applied is mediation (intervening). The results of this study show that the training variable does not have a significant positive effect on productivity; training has a significant positive effect on both engagement and competence; engagement has a significant positive effect on productivity; competence does not have a significant effect on productivity; engagement does not have a significant effect in mediating the relationship between training and productivity; and competence successfully mediates the relationship between training and productivity. The findings of this study are expected to help improve work productivity levels among oil palm farmers in Nehas Liah Bing Village, East Kutai Regency.